1996
DOI: 10.1017/s1357729800014533
|View full text |Cite
|
Sign up to set email alerts
|

The influence of day length and temperature on food intake and growth rate of bulls given concentrate or grass silage ad libitum in two housing systems

Abstract: In order to study the effect of day length and temperature on performance, data from 495 growing, non-castrated bulls of the Swedish Red and White breed were analysed. Groups of 11 bulls were housed in either an insulated building in pens having slatted floors or in an uninsulated building with pens having both a deep straw bed and a concrete floor. The majority of the bulls (330) were given a concentrate diet ad libitum, while the remainder (165) were given grass silage ad libitum supplemented with concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…The pLWG showed a clear maximum which preceded the longest day by about 1 month and a minimum at 1 month before the shortest day. The difference between trough and peak LWG estimated by Mossberg and Jonsson (1996) for a 200-kg calf given a concentrate diet ad libitum, is between 1-25 and 1-55 kg/day ( Figure, 4 of Mossberg and Jonsson, 1996) slightly larger than the difference estimated in the present study. Figure 3 presents the combined effects of age and of photoperiod on gain in a three-dimensions chart (model 1).…”
Section: Resultscontrasting
confidence: 73%
See 2 more Smart Citations
“…The pLWG showed a clear maximum which preceded the longest day by about 1 month and a minimum at 1 month before the shortest day. The difference between trough and peak LWG estimated by Mossberg and Jonsson (1996) for a 200-kg calf given a concentrate diet ad libitum, is between 1-25 and 1-55 kg/day ( Figure, 4 of Mossberg and Jonsson, 1996) slightly larger than the difference estimated in the present study. Figure 3 presents the combined effects of age and of photoperiod on gain in a three-dimensions chart (model 1).…”
Section: Resultscontrasting
confidence: 73%
“…The upper limit of pLWG at each date was distinct, and the pLWG below this limit was diffused, because of the positive age and negative age 2 effects of this regression. Chemineau et al, 1992) but all the studies that examined the response of quantitative traits such as food intake (Ingvartsen et al, 1992;Walkden-Brown et al, 1994;Mossberg and Jonsson, 1996), milk yield (Kashiwamura et al, 1991) and growth rate (Mossberg and Jonsson, 1996) suggest a progressive response to photoperiod. The highest gain was predicted for 19 May, and the lowest for 18 November, which means that the gain sinusoid preceded that of the day length by 33 days, as a result of the combined positive effects of DL and DLC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes observed in the growth rate or milk yield of ruminants with long day length appear to be independent of nutrient intake (Forbes, 1982;Petitclerc et al, 1983;Phillips and Schofield, 1989;Mossberg and Jonsson, 1996), although ad libitum 173 food availability increased the stimulatory effect of long day length on the growth rate of sheep (Forbes et al, 1981). However, Forbes et al (1979) observed that in sheep at least half of the observed increase in body weight is due to changes in the weight of the contents of the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 98%
“…Peters et ah, 1980;Mossberg and Jonsson, 1996), while others show no effect (e.g. Some have shown increased growth rates with long day length light (e.g.…”
Section: Introductionmentioning
confidence: 99%